Regaining Cross-Border Authority: The Role of Law and Institutional Challenges for Curators in Cross-Border Insolvency - Indrawan, Riesky; Situmorang, Risma; Darodjat, Tubagus Achmad (CV. Era Digital Nusantara, 2025)
The increasing integration of the global economy has led to a surge in cross-border insolvency cases, placing insolvency administrators as key actors in the management and liquidation of assets across jurisdictions. This article critically examines the legal role of insolvency administrators in cross-border insolvency cases and identifies normative and structural challenges that hinder the effectiveness of their duties. Using a normative legal method and a comparative approach, this study analyzes the weak legal recognition of foreign insolvency administrators, the failure of intergovernmental coordination, and the limitations in asset tracing due to data access restrictions between jurisdictions. Findings reveal that the absence of a harmonized legal framework and the lack of formal transnational cooperation protocols significantly hinder the legitimacy and efficiency of the role of bankruptcy trustees in a global context. This study also highlights regulatory gaps in Indonesian bankruptcy law that have not yet accommodated mechanisms for cross-border recognition and cooperation. Using the lens of doctrinal legal theory and transnational legal theory, this article proposes institutional reforms through the adoption of the UNCITRAL Model Law and the development of cooperation protocols among insolvency administrators as solutions toward a more responsive and equitable global insolvency governance system. This article contributes both theoretically and practically to the development of an inclusive and interoperable insolvency system within the global legal order.